Kekuatan Tokoh Kinan Sebagai Perempuan Dalam Novel Layangan Putus Karya Mommy ASF - Mukti Lestari, Indah; Maharani Umaya, Nazla; Nayla, Azzah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
The background of this research is based on the view that women, often considered weak and treated unfairly, in fact possess extraordinary potential strength. This study aims to describe the strength of women in the novel Layangan Putus by Mommy ASF. The novel, which gained popularity for addressing domestic issues, was chosen as the object of research because it reflects social realities and the struggles of women. The data presentation technique in this study uses a qualitative descriptive method, with liberal feminism employed to analyze women’s strength from the perspectives of equal rights, freedom, and rational capability. The research data consist of texts, quotations, plotlines, character names, and characterization. Data collection techniques include literature study as well as reading and note-taking, while data analysis uses descriptive techniques to identify, classify, and interpret the findings. The results of the study show that women’s strength in the novel Layangan Putus is manifested through the central character, Kinan, who demonstrates multiple forms of strength. Based on Robert Havighurst’s concept, Kinan possesses emotional, economic, intellectual, and social independence. According to Gandhi, Kinan is portrayed as a woman who is self-reliant, capable of sustaining her family, and providing financial support. Meanwhile, Rahadiani & Zulfiningrum highlight Kinan’s freedom of expression, courage in decision-making, and resilience as an independent woman. This strength does not only come from within herself but is also reinforced by the support of her family, children, friends, and social relations, enabling her to rise after facing domestic conflicts. Thus, the novel successfully portrays women as resilient, empowered, and capable of rebuilding their lives through self-potential and the support of their social environment.